LIGHT VERB CONSTRUCTIONS IN LEGAL TRANSLATION FROM POLISH INTO GERMAN - SIEWERT-KOWALKOWSKA, Katarzyna (Comparative Legilinguistics, 2016)
Characterizing the German legal language at a syntactic level, the researchers point to the frequent use of structures called light verb constructions (Ger. Funktionsverbgefüge). The article attempts to present this phenomenon in the context of legal translation into Polish. The theoretical part includes the characteristics of a formal verbal phrases syntax and a description of their syntactic and semantic properties. The empirical part presents the analysis of dictionary equivalents and equivalents which appear in the Polish translation of the selected two German acts of law. The article focuses on translation solutions in order to formulate general conclusions concerning potential solutions for Polish translation of these constructions.